The Juridical Continental Shelf In The Bay Of Bengal, According To The Statement Of Understanding - Mridha, Abul Hasan; Macnab, Ron; Varma, Herman (The International Hydrographic Review, 2006)
In its Final Act, the Third UN Law of the Sea Conference approved a modification of the sediment thickness rule of Article 76, enshrining it in a Statement of Understanding. This paper outlines the provisions of the Statement as they might apply in the Bay of Bengal, comparing the outcome to that derived from a strict implementation of the provisions of Article 76. It also identifies a few problem areas where legal interpretations are needed to clarify the technical criteria of the Statement and their scope of application, e.g. does the Statement apply only in the Bay of Bengal, or can it apply elsewhere?